Temporal dynamics of halogenated organic compounds in Marcellus Shale flowback. (1st June 2018) - Luek, Jenna L.; Harir, Mourad; Schmitt-Kopplin, Philippe; Mouser, Paula J.; Gonsior, Michael
Abstract: The chemistry of hydraulic fracturing fluids and wastewaters is complex and is known to vary by operator, geologic formation, and fluid age. A time series of hydraulic fracturing fluids, flowback fluids, and produced waters was collected from two adjacent Marcellus Shale gas wells for organic chemical composition analyses using ultrahigh resolution mass spectrometry. Hierarchical clustering was used to compare and extract ions related to different fluid ages and many halogenated organic molecular ions were identified in flowback fluids and early produced waters based on exact mass. Iodinated organic compounds were the dominant halogen class in these clusters and were nearly undetectable in hydraulic fracturing fluid prior to injection. The iodinated ions increased in flowback and remained elevated after ten months of well production. We suggest that these trends are mainly driven by dissolved organic matter reacting with reactive halogen species formed abiotically through oxidizing chemical additives applied to the well and biotically via iodide-oxidizing bacteria. Understanding the implications of these identified halogenated organic compounds will require future investigation in to their structures and environmental fate. Graphical abstract: Highlights: FT-ICR-MS reveals temporal changes in shale gas well organic chemical composition. Many organohalogens in fluid were unique to the first 3 months of well operation. Iodinated organic ions in fluid remain abundant over 10 months of well operation. Abiotic and biotic reactions may drive iodinated organic compound formation.